Audio-Visual Media as an Innovation in Learning Basic Volleyball Passing Movements to Increase Interest in Learning - Nada Amelia Prasetyanti; Mochamad Ridwan (Ilmu Olahraga, 2026)
The use of audio-visual media is crucial for increasing the effectiveness of the learning process because it combines images and sounds that engage students. The purpose of this study was to determine changes in students' learning interest in learning using audio-visual media. This study aimed to determine the effect of applying audio-visual media on increasing students' learning interest in learning basic volleyball overhead passing movements. Researchers collected data using a quantitative approach and pre-experimental design using a one-group pretest-posttest design. Treatment was given for four meetings using audio-visual media with 60 eighth-grade students at MTs Sunan Giri. To measure students' learning interest, whose validity and reliability had been tested, researchers used a Likert scale questionnaire. Researchers used the SPSS application to analyze data with the Kolmogorov-Smirnov and Shapiro-Wilk normality tests. After implementing learning using audio-visual media, students' learning interest increased significantly. When compared, the posttest results were higher than the pretest results, indicating that during the learning process, the use of audio-visual media was effective in increasing students' enthusiasm. Students benefit greatly from audiovisual media, enabling them to understand the basic movements of the overhead pass more concretely through engaging and clear visual displays. It can be concluded that the use of audiovisual media can make learning more effective and innovative, increasing student interest in learning. Therefore, it can be concluded that the use of audiovisual media is an effective learning innovation for increasing student interest in learning